Adrenal Vein Sampling in the Young – Necessary or Not? - Gkaniatsa, Eleftheria; Ragnarsson, Oskar (Experimental and Clinical Endocrinology & Diabetes, 2023)
Current clinical guidelines from the US Endocrine Society state that adrenal venous sampling (AVS) may not be necessary in patients younger than 35 years with marked aldosteronism and a solitary adrenal adenoma on imaging. At the time when the guidelines were published, only one study supported the statement, a study that included 6 patients younger than 35 years, all of whom had unilateral adenoma on imaging and unilateral primary aldosteronism (PA), according to AVS. Since then, to our knowledge, four additional studies have been published that provide data on concordance between conventional imaging and AVS among patients younger than 35 years. In these studies, 7 of 66 patients with unilateral disease on imaging had bilateral disease, according to AVS. We find it, therefore, reasonable to conclude that imaging studies alone inaccurately predict laterality in a significant number of young patients with PA and that available data challenge the current clinical guidelines.
Keywords: primary aldosteronism; adrenal vein sampling; mineralocorticoid receptor antagonist; adrenalectomy; clinical guidelines